Comparison of pharmacokinetic profiles of seven major bioactive components in normal and non-alcoholic fatty liver disease (NAFLD) rats after oral administration of Ling-Gui-Zhu-Gan decoction by UPLC-MS/MS - Nie, Wenlong; Yang, Yang; Li, Ling; Ding, Yue; Chen, Xingmi; Li, Ming; He, Ning; Ji, Guang; Zhang, Yong; Kang, Ping; Zhang, Tong (Frontiers in Pharmacology, 2023)
A sensitive and rapid ultra-performance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS) method was hereby developed for the determination of seven components, namely, glycyrrhizic acid, glycyrrhetinic acid, dehydrotumulosic acid, isoliquiritin, liquiritin, atractylenolide III, and cinnamic acid, in the plasma of rats after the oral administration of Ling-Gui-Zhu-Gan decoction (LGZGD). Besides, this very method was methodologically validated for specificity, linearity, inter-day and intra-day precision, accuracy, matrix effect, extraction recovery, and stability. It was also successfully used for the first time to compare the pharmacokinetic characteristics of the seven components after oral administration of LGZGD to normal rats and non-alcoholic fatty liver disease (NAFLD) rats. The results indicated significant differences between the pharmacokinetic characteristics of normal and NAFLD rats. To further reveal the different pharmacokinetic behaviors, the expressions of enzymes and transporters in the liver of normal and NAFLD rats were detected using UPLC-MS/MS. In the NAFLD rats, UDP-glucuronosyltransferase 1-1 (UGT1A1) and nine transporters were significantly inhibited and a positive correlation was observed between them and the AUC of the major components. The present results indicate that the pharmacokinetic differences between the normal and NAFLD rats might be attributed to the significant lower expression levels of both the metabolic enzyme UGT1A1 and nine transporter proteins in the NAFLD rats than in the normal rats. Meanwhile, UGT1A1 and the nine transporter proteins might be used as potential biomarkers to assess the ameliorative effect of LGZGD on NAFLD, which could provide useful information to guide the clinical application of LGZGD.